Ospitalità Italiana, Italia, L’Italia, a diachronic study of the translation of tourist discourse in ENIT multilingual magazines (Altre Modernità, 2025)
This paper sets out to shed light on the evolution of cross-cultural communication strategies used to promote Italy to foreign visitors, focusing on the multilingual magazines published between 1930 and 1959 by ENIT. For one hundred years, since its foundation in October 1919, ENIT has been responsible for promoting Italy as a tourist destination worldwide. Based on the preliminary results of the DIETALY research project,1 which deals with a large body of printed promotional material published by ENIT in English Language, this paper examines the Italian Tourism Board’s communication strategies, as well as intercultural and translation issues, focusing primarily on the verbal content of early multilingual magazines.
Keywords: Italian tourist communication; cross-cultural tourist promotion; tourism discourse and translation; diachronic study on the language of tourism; ENIT multilingual magazines